Do family firms perform better? Evidence from Singapore Exchange - Kee, Lee Teck (2016)
Existing literature have established family firms as a common form of firm ownership type but there have been mixed results on their performance as compared to non-family firms. Furthermore, three main strands of literature are identified to relate closely to firm performance. Firstly, the relation between family ownership and firm performance (Kimber et al. 2005; Peng & Jiang, 2010). Secondly, the relation between family firm management types and firm performance (Sraer & Thesmar, 2007). Thirdly, the relation of board characteristics and firm performance (Mak & Li, 2001; Nguyen et al., 2014). However, these relations are not discussed together in many studies. Also, results from previous studies may not conclusively apply to the business climate in Singapore. Therefore, our paper seeks to fill in these research gaps through the study of firms listed on the Singapore Exchange. Our results show that, (1) family firms perform 4% higher than private (non-family) firms in terms of Return on Assets. (2) founder CEOs and professionally-hired CEOs family firms perform better than private firms, with 4% and 6% higher Return on Assets respectively. (3) For analysis of board characteristics, a smaller board size in family firms is associated with better firm performance and our dataset do indeed reflect that family firms have a significantly smaller board size than private firms. This implies that smaller board size among family firms is likely to be a crucial driving force behind family firms‘ higher performance over private firms.